Household satisfaction with health services and response strategies to malaria in mountain communities of Uganda - Aggrey, Siya; Egeru, Anthony; Kalule, John Bosco; Lukwa, Akim Tafadzwa; Mutai, Noah; Hartnack, Sonja (Oxford Academics, 2025)
Measuring satisfaction with health service delivery in fragile communities provides an opportunity to improve the resilience of health systems to threats including climate change. Additionally, understanding factors associated with the choice of response strategies to certain public health threats provides an opportunity to design context-specific interventions.BACKGROUNDMeasuring satisfaction with health service delivery in fragile communities provides an opportunity to improve the resilience of health systems to threats including climate change. Additionally, understanding factors associated with the choice of response strategies to certain public health threats provides an opportunity to design context-specific interventions.We used polytomous latent class analyses to group participants' responses and an additive Bayesian modelling network to explore satisfaction with health service delivery as well as factors associated with response strategies of households to malaria. We did this with a focus on the rural parts of Uganda in Mount Elgon.METHODSWe used polytomous latent class analyses to group participants' responses and an additive Bayesian modelling network to explore satisfaction with health service delivery as well as factors associated with response strategies of households to malaria. We did this with a focus on the rural parts of Uganda in Mount Elgon.We found that approaches to malaria control and management at household level include the use of traditional (54.5%), private (20.5%) and publicly available services (25%). Regarding satisfaction with health services, 66.6% of respondents were satisfied with health service components of information flow, drug/vaccine access and accessibility. Type of housing, livelihood sources, previous malaria experience and health services were strongly associated with responses to malaria occurrence at household level. The rest of the factors were weakly associated with malaria responses.RESULTSWe found that approaches to malaria control and management at household level include the use of traditional (54.5%), private (20.5%) and publicly available services (25%). Regarding satisfaction with health services, 66.6% of respondents were satisfied with health service components of information flow, drug/vaccine access and accessibility. Type of housing, livelihood sources, previous malaria experience and health services were strongly associated with responses to malaria occurrence at household level. The rest of the factors were weakly associated with malaria responses.The indigenous interventions utilised by households to manage and control malaria were largely dependent on their satisfaction with health service delivery components. Interventions thus ought to leverage local existing knowledge to optimise outcomes and ensure sustainable health.CONCLUSIONSThe indigenous interventions utilised by households to manage and control malaria were largely dependent on their satisfaction with health service delivery components. Interventions thus ought to leverage local existing knowledge to optimise outcomes and ensure sustainable health. MEDLINE - Academic